Visión desde Colombia del impacto de la matemática moderna y el papel del CIAEM - Arboleda, Luis Carlos (2019)
This intervention within the Plenary Roundtable on the history of IACME will focus on analyzing the social and political context in which the First Inter-American Conference on Mathematics Education (IACME I) of 1961 was held in Bogotá. In particular, the inaugural speeches of the two most important authorities present at the meeting are examined: Jaime Posada Díaz, Colombian Minister of Education; and the esteemed mathematician Marshall Stone. Background differences will be shown in the way politicians and academics represented the importance of the Conference in terms of purposes, criteria and procedures to promote the reform of Mathematics Education in the hemisphere.